The effect of isolated or combined small-sided games and speed endurance training on physical performance parameters in young soccer players (Kinesiology, 2021)
The purpose of this study was to investigate the effects of six weeks of small-sided games (SSG), speed endurance (SER) and combined SSG and SER (CT) training programs on sprint, repeated sprint, Yo-Yo intermittent recovery test level 1 (Yo-Yo IR1) and level 2 (Yo-Yo IR2) performance in young soccer players. Forty-one elite young soccer players (body height: 174.0 ± 7.5 cm, body weight: 59.7 ± 9.5 kg, age: 14.6 ± 0.5 years, training age: 7.4 ± 0.6 years) underwent anthropometric measurements before performing 10m and 30m sprint tests, repeated sprint tests, and Yo-Yo IR1 and Yo-Yo IR2. The players were then divided into four groups: the SSG group (SSG; n=11), the SER group (SER; n=10), the CT group (CT; n=11), and the control group (CG; n=9). All groups performed training for six weeks on two days out of the five training days the participants were undertaking. There was a statistically significant increase in the Yo-Yo IR1 and Yo-Yo IR2 test performances of players in SSG, SER and CT groups (p